2021
DOI: 10.1186/s13256-021-03101-z
|View full text |Cite
|
Sign up to set email alerts
|

Rapid resolution of severe exudation in uveal effusion syndrome with anti-vascular endothelial growth factor alone in a case of bilateral nanophthalmos: a case report

Abstract: Background Uveal effusion syndrome is a rare disease characterized by exudative detachments of the choroid, ciliary body, and retina. Various surgical procedures and nonsurgical strategies have been described to treat uveal effusion syndrome with limited success. The treatment for uveal effusion syndrome remains a serious challenge for clinicians. To the best of our knowledge, no previous report has described a severe uveal effusion syndrome patient with nanophthalmos treated by using an anti-v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…14,25 In addition, cases of successful UES treatment have been reported after administration of intravitreal anti-VEGF injections. 15,17 This study has several limitations that should be acknowledged. First, it was retrospective in nature, with inherent biases and limitations associated with data collection and analysis.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…14,25 In addition, cases of successful UES treatment have been reported after administration of intravitreal anti-VEGF injections. 15,17 This study has several limitations that should be acknowledged. First, it was retrospective in nature, with inherent biases and limitations associated with data collection and analysis.…”
Section: Discussionmentioning
confidence: 96%
“…4,9,10 Medical treatment, including systemic or periocular corticosteroids, 11 oral carbonic anhydrase inhibitors 12 or nonsteroidal anti-inflammatory drugs, 13 and topical prostaglandin analogues, 14 has yielded variable results, demonstrating significant efficacy in some cases, while resulting in equivocal outcomes in others. Recently, the use of intravitreal antivascular endothelial growth factor (VEGF) agents alone 15 or in combination with surgical intervention 16,17 has been reported as a treatment option in a limited number of UES cases. Nonetheless, owing to the rarity of UES, few studies have comprehensively reported its long-term prognosis and associated factors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are anecdotal reports of the use of medical therapy for exudative RD in nanophthalmos, such as corticosteroids, 29 nonsteroidal anti-inflammatory drugs, 6,30 and intravitreal vascular endothelial growth factor. 31 Medical therapy with oral corticosteroids in uveal effusion syndrome is well established but was deemed ineffective in nanophthalmos. 10,11 Elgin et al 9 described a patient with nanophthalmos and mild exudative RD that resolved rapidly after administration of the topical corticosteroid alone.…”
Section: Discussionmentioning
confidence: 99%
“…The molecular target is vascular endothelial growth factor, which upregulates new blood vessel growth, and pathological vasculature formation. While the exact therapeutic mechanism of anti-VEGF agents in UES remains unclear, Guo et al reported resolution of three intractable cases of UES, and Song et al reported success in one case of nanophthalmic UES [ 71 , 72 ]. One hypothesis is that the increased expression of interleukin (IL)-6, IL-8, and VEGF in UES affects vessel permeability and choroidal congestion.…”
Section: Emerging Medical Therapiesmentioning
confidence: 99%